Climate‐Sensitive Controls on Large Spring Emissions of CH4 and CO2 From Northern Lakes. Issue 7 (29th July 2019) - Jansen, J.; Thornton, B. F.; Jammet, M. M.; Wik, M.; Cortés, A.; Friborg, T.; MacIntyre, S.; Crill, P. M.
Abstract: Northern lakes are important sources of the climate forcing trace gases methane (CH4 ) and carbon dioxide (CO2 ). A substantial portion of lakes' annual emissions can take place immediately after ice melt in spring. The drivers of these fluxes are neither well constrained nor fully understood. We present a detailed carbon gas budget for three subarctic lakes, using 6 years of eddy covariance and 9 years of manual flux measurements. We combine measurements of temperature, dissolved oxygen, and CH4 stable isotopologues to quantify functional relationships between carbon gas production and conversion, energy inputs, and the redox regime. Spring emissions were regulated by the availability of oxygen in winter, rather than temperature as during ice‐free conditions. Under‐ice storage increased predictably with ice‐cover duration, and CH4 accumulation rates (25 ± 2 mg CH4 ‐C·m −2 ·day −1 ) exceeded summer emissions (19 ± 1 mg CH4 ‐C·m −2 ·day −1 ). The seasonally ice‐covered lakes emitted 26–59% of the annual CH4 flux and 15–30% of the annual CO2 flux at ice‐off. Reduced spring emissions were associated with winter snowmelt events, which can transport water downstream and oxygenate the water column. Stable isotopes indicate that 64–96% of accumulated CH4 escaped oxidation, implying that a considerable portion of the dissolved gases produced over winter may evade to the atmosphere. Plain Language Summary: Northern lakes are globally significant sources of greenhouse gases methane and carbon dioxide, but the seasonal pattern of emissions from lakes that are ice covered in winter remains poorly resolved. Our multiyear, multilake study reveals the importance of emissions during the ice‐off period, when carbon gas that had accumulated under ice is released. We show that more than half of the annual methane emissions and a third of the yearly carbon dioxide flux can be released at spring ice‐out. Unlike emissions during summer, which tend to be closely correlated with temperature, spring emissions of both gases are in part regulated by the availability of oxygen under ice. The quantity of carbon gas accumulating under ice, and therefore the amount that can be emitted in spring, scales predictably with ice‐cover duration. Parameterizations of winter and spring carbon cycling processes, such as those described in this study, may contribute to more accurate models of annual, ecosystem‐level carbon fluxes and are essential tools to improve freshwater emission inventories and quantify critical Arctic warming feedbacks. Key Points: Multiyear flux measurements show that annual CH4 emissions from northern lakes can be dominated by emissions during ice‐off in spring CH4 accumulates under ice at rates exceeding summer emissions, in part because prolonged anoxia limits methanotrophy Under‐ice carbon gas storage scales predictably with ice‐cover season length, but meltwater advection or dilution can limit fluxes in spring